Portable sample processing for molecular assays: application to Zika virus diagnostics. Issue 9 (31st March 2022) - Narahari, Tanya; Dahmer, Joshua; Sklavounos, Alexandros; Kim, Taehyeong; Satkauskas, Monika; Clotea, Ioana; Ho, Man; Lamanna, Julian; Dixon, Christopher; Rackus, Darius G.; Silva, Severino Jefferson Ribeiro da; Pena, Lindomar; et al.
Abstract : A digital microfluidic system was developed for portable Zika virus diagnosis, featuring integrated, automated sample extraction and amplification. Abstract : This paper introduces a digital microfluidic (DMF) platform for portable, automated, and integrated Zika viral RNA extraction and amplification. The platform features reconfigurable DMF cartridges offering a closed, humidified environment for sample processing at elevated temperatures, as well as programmable control instrumentation with a novel thermal cycling unit regulated using a proportional integral derivative (PID) feedback loop. The system operates on 12 V DC power, which can be supplied by rechargeable battery packs for remote testing. The DMF system was optimized for an RNA processing pipeline consisting of the following steps: 1) magnetic-bead based RNA extraction from lysed plasma samples, 2) RNA clean-up, and 3) integrated, isothermal amplification of Zika RNA. The DMF pipeline was coupled to a paper-based, colorimetric cell-free protein expression assay for amplified Zika RNA mediated by toehold switch-based sensors. Blinded laboratory evaluation of Zika RNA spiked in human plasma yielded a sensitivity and specificity of 100% and 75% respectively. The platform was then transported to Recife, Brazil for evaluation with infectious Zika viruses, which were detected at the 100 PFU mL −1 level from a 5 μL sample (equivalent to an RT-qPCR cycle threshold value of 32.0), demonstrating its potential as a sample processing platform for miniaturized diagnostic testing.